ANALISIS KELAYAKAN INVESTASI DAN MONITORING USAHA BUDIDAYA IKAN BANDENG SECARA INTENSIF BERBASIS WEB DI SIDAYU KABUPATEN GRESIK - Moritian, Dio Ichwandoko; Tanuwijaya, Haryanto; Widodo, Arifin Puji (Jurnal JSIKA, 2013)
An investor need investment requirements planning, cost requirements planning, revenue planning, and determine the appropriateness of an investment before  start cultivation milkfish  intensively. Because investors during these often fail in establishing cultivation milkfish  intensively in Sidayu, Gresik regency. There are currently no applications for investor to make investment requirements planning, cost requirements planning, calculation of income planning, calculation of return on investment, determining the feasibility of investment, and monitoring the evaluation of implementation calculation planning of cultivation milkfish  intensively. One solution to overcome these obstacles is to make the application feasibility analysis of investment and monitoring of cultivation milkfish intensively web-based. This system built to analyze the feasibility of investment and monitoring the cultivation milkfish intensively use key performance indicator (KPI) event which make the user to know whether the evaluation of implementation of the results of calculations performed already reach the target.” Keywords : Application feasibility analysis of investment, Monitoring, KPI, Milkfish.